Hyperglycemia in pregnancy did not worsen the short-term outcomes of very preterm infants: a propensity score matching study - Li, Ying; Shen, Wei; Zhang, Rong; Mao, Jian; Liu, Ling; Chang, Yan-Mei; Ye, Xiu-Zhen; Qiu, Yin-Ping; Ma, Li; Cheng, Rui; Wu, Hui; Chen, Dong-Mei; et al. (Frontiers in Pediatrics, 2024)
Background Hyperglycemia in pregnancy (HGP) has generally been considered a risk factor associated with adverse outcomes in offspring, but its impact on the short-term outcomes of very preterm infants remains unclear. Methods A secondary analysis was performed based on clinical data collected prospectively from 28 hospitals in seven regions of China from September 2019 to December 2020. According to maternal HGP, all infants were divided into the HGP group or the non-HGP group. A propensity score matching analysis was used to adjust for confounding factors, including gestational age, twin or multiple births, sex, antenatal steroid administration, delivery mode and hypertensive disorders of pregnancy. The main complications and the short-term growth status during hospitalization were evaluated in the HGP and non-HGP groups. Results A total of 2,514 infants were eligible for analysis. After matching, there were 437 infants in the HGP group and 874 infants in the non-HGP group. There was no significant difference between the two groups in main complications including respiratory distress syndrome, bronchopulmonary dysplasia, necrotizing enterocolitis, retinopathy of prematurity, patent ductus arteriosus, culture positive sepsis, intraventricular hemorrhage, periventricular leukomalacia, anemia, feeding intolerance, metabolic bone disease of prematurity, or parenteral nutrition-associated cholestasis. The incidences of extrauterine growth retardation and increased growth retardation for weight and head circumference in the non-HGP group were all higher than those in the HGP group after matching (P < 0.05). Conclusions HGP did not worsen the short-term outcomes of the surviving very preterm infants, as it did not lead to a higher risk of the main neonatal complications, and the infants’ growth improved during hospitalization.